EVALUASI KONSEP PENGEMBANGAN TAMAN BISNIS BERDASARKAN KARAKTERISTIK KAWASAN CAMPURAN - Burhani, Nabila Abdurrahman; Cahya, Darmawan Listya; Martini, Elsa; Aditianata (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
Mixed-use development has become common in many major cities around the world. The use of mixed-use development has also occurred in Indonesia since the 2000s, with the Jakarta Metropolitan Urban Area being one of the cities that has implemented it extensively. The implementation is intended to address urban issues caused by uncontrolled urbanization, such as traffic congestion, the need for proper housing, and the issue of limited land. One of the efforts for land efficiency and becoming a compact and sustainable city is the concept of mixed area development. One of the business areas that has been transformed from a warehouse area to a mixed area is CIBIS Business Park, which spans approximately 12 hectares and is located in the South Jakarta Administrative City area. Mixed area development should ideally meet all of the criteria for mixed area characteristics, but it turns out that there are many mixed area developments that do not meet the mixed area characteristic criteria, resulting in new problems both in the mixed area and surrounding it. The purpose of this study is to evaluate whether the CIBIS Business Park's concept of mixed-use development meets the criteria for mixed-use characteristics, specifically the diversity of use criteria and design criteria. The research method used in this study is quantitative research, and the evaluation method is based on the plan's concept (ex-ante evaluation). This evaluation method compares the CIBIS Business Park area's site plan to the criteria for mixed-use development characteristics, specifically the diversity of use criteria and design criteria. According to the evaluation results, the CIBIS Business Park development concept in general conforms to the characteristics of a mixed area, with 71.42% meeting the criteria for diversity of use and 57.14% meeting the design criteria